The Use of Instagram Integrated Learning Media Against Student Learning Motivation in Reaction Rate Material - Widarti, Hayuni Retno; Yamtinah, Sri; Mawardi, Mawardi; Rokhim, Deni Ainur; Syafruddin, Afis Baghiz; Baharsyah, Allykha (Universitas Negeri Surabaya, 2023)
The purpose of this study was to determine the effect of using Instagram integrated learning media on students' learning motivation in the matter of reaction rate. This study used a qualitative descriptive method by using a questionnaire to find out the increase in the results of students' learning motivation. This research was conducted at one of the public high schools in Malang City involving 33 students of class XI IPA 4. The data analysis used was in the form of a qualitative test of students' learning motivation. The results of the study show that the use of Instagram learning media can increase students' learning motivation regarding the reaction rate material.